Numerical Analysis of the Effect of Coal Seam Characteristics on the Longwall Top Coal Cavability - Tien Dung Le; Joung Oh; Bruce Hebblewhite; Chengguo Zhang; Rudrajit Mitra (International Conference on Ground Control in Mining, 2017)
"Geomechanical and geotechnical characteristics of coal seam are important parameters that directly affect the cavability of top coal in the longwall top-coal caving (LTCC) method. The impact of these parameters such as coal strength, coal deformation modulus, coal discontinuities and top-coal thickness on cavability has not been fully understood in previous numerical analyses. The limitation and selection of the numerical modelling codes were two of the main reasons. In this paper, detailed caving simulations are performed using a 2D distinct element method (DEM) code, UDEC, to study the effect of various critical parameters on top-coal cavability. The numerical analysis evidently shows that the coal deformation modulus, coal discontinuities, and top-coal thickness have considerable influences on cavability. Coal strength is also a factor but to a lesser extent. The results presented in this paper contribute to the understanding of top-coal cavability in different mining environments and facilitate the development of an advanced cavability evaluation criterion. INTRODUCTION The longwall top-coal caving (LTCC) method was originally developed in the 1950s in the former Soviet Union and France (Tien, 1998). The method was nearly abandoned in Europe after the mid-1980s; however, it has been significantly improved and widely applied in China since the late 1980s. A conceptual model of the LTCC method is shown in Figure 1 in which a thick coal seam is divided into two sections including the lower or cutting section, and the upper or top coal section. The lower section of coal seam is mined by conventional longwall method. Meanwhile, the upper section is recovered by caving through the face support. The LTCC method is considered to be the most viable option for mining general thick seams. Compared to the multi-slice longwall (MSL) method, LTCC has the major advantages (Zhongming, 2001; cited by Vakili, 2009):"